Financialisation Reinforced: The Enduring Legacy of the Covid Pandemic - Photis Lysandrou; Taimaz Ranjbaran (City, University of London, City Political Economy Research Centre (CITYPERC), 2021)
This paper examines the impact of the covid pandemic on the financialisation process, here viewed as the growing domination of the world's financial securities markets over the world's material output base. Two major arguments are advanced. The first is that the pandemic has reinforced the functionality of financial market scale, which is that its continuing growth signifies nothing other than that governments and corporations on the one hand and pension funds and other asset managers on the other are colonising the future to cope with the rising financial pressures of the present. The second argument is that the pandemic has also accentuated one of the more notable dysfunctional aspects of the continuing growth of financial market scale, which is the reinforcement of a core-periphery divide between the advanced and emerging market economies that occupy the global financial system. The paper concludes with some policy implications of the analysis that includes the call for a global wealth tax.
Keywords: G20; G23; 330; financialisation; covid pandemic; colonisation of the future; core-periphery divide; global wealth tax